TINJAUAN HUKUM ISLAM DALAM PRAKTIK JUAL BELI TANAH TAHUNAN DI LINGKUNGAN KARANG ANYAR KELURAHAN PAGESANGAN TIMUR KOTA MATARAM - Khairul Hadi; Fariz Al-Hasni (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2021)
The annual process of buying and selling land in the Karang Anyar East Pagesangan neighborhood of Mataram City has been an activity that has been going on for years, but problems arise when the current season's harvest is uncertain, those who have rented agricultural land or rice fields to someone for a long period of time certain time while the rental period has expired. This incident is still a problem in the Karang Anyar community, because some owners ask for additional or unilateral compensation from tenants for excess time and other parties prefer to continue the transaction process until the harvest arrives.